NBA players` pay and performance: What counts? - Sigler, K.; Compton, W. (The Sport Journal, 2018)
The stars in the National Basketball Association (NBA) are paid handsomely. In the 2017-18 season Stephen Curry received over $34.7 million and LeBron James made over $33.3 million on the court. Prior studies show that players are paid for points scored, rebounds, experience, assists, blocks, field goal percentage and fouls. But the NBA is evolving. Teams over the years have gone from seldom shooting the 3-point shot to making it the focus of their offense. Analytics that first received much attention in baseball with the money ball phenomenon are now in all sports as well. This study accounts for the change in the game by not only including significant variables from prior studies but by also incorporating the 3-point shot and the Hollinger player efficiency rating (PER) in analyzing what counts in determining NBA players` pay. The researchers find that points, player experience (years in the league), assists, rebounds and fouls are statistically significant factors when it comes to paying NBA players but we also discover that 3-point shots made and Hollinger`s PER are insignificant. In addition, the researchers perform a backward stepwise regression eliminating insignificant independent variables one at a time (least significant each time) until the model includes only significant variables. Again, the same variables are statistically significant although the statistics for the stepwise model improve over the original model.